Prevalence and risk factors for avian influenza virus (H5 and H9) contamination in peri-urban and rural live bird markets in Bangladesh - Islam, Ariful; Islam, Shariful; Islam, Monjurul; Hossain, Mohammad Enayet; Munro, Sarah; Samad, Mohammed Abdus; Rahman, Md. Kaisar; Shirin, Tahmina; Flora, Meerjady Sabrina; Hassan, Mohammad Mahmudul; Rahman, Mohammed Ziaur; Epstein, Jonathan H. (Frontiers in Public Health, 2023)
Avian influenza viruses (AIV) have been frequently detected in live bird markets (LBMs) around the world, primarily reported in urban areas, and have the potential to spillover to other species, including humans. However, the contamination of AIV environmental surfaces in rural LBMs is poorly documented. Hence, we conducted this study to assess the prevalence of AIV subtypes and identify the risk factors associated with AIV positivity in peri-urban and rural LBMs in Bangladesh. Between 2017 and 2018, we collected 200 pooled fecal and offal samples in 63 LBMs and tested for the AIV matrix gene (M-gene), followed by H5, H7, and H9 subtypes using real-time reverse transcriptase-polymerase chain reaction (rRT-PCR). We performed a descriptive analysis to assess hygiene and sanitation practices, AIV subtypes by species, sample types, and landscape conversions of LBMs. We conducted a univariable analysis followed by generalized linear mixed model (GLMM) to identify the associated risk factors of AIV contamination at LBMs. The physiographic and hygienic practices and AIV circulation were significantly varied in rural and peri-urban LBMs. The stall level prevalence of AIV was 42.5% (95% CI: 35.56–49.67), and that of A/H5, A/H9, and A/Untyped was 10.5%, 9%, and 24.0%, respectively. We did not detect A/H7. In GLMM, we found land gradient (AOR: 3.02; 95% CI: 1.18-7.72), the number of chicken strains at stall (AOR: 2.4; 95% CI: 1.01-5.67), source of birds (AOR: 2.35; 95% CI: 1.0-5.53), separation of sick birds (AOR: 3.04; 95% CI: 1.34-6.92), disposal of waste/dead birds (AOR: 3.16; 95% CI: 1.41-7.05), a cleaning agent (AOR: 5.99; 95% CI: 2.26-15.82), access of dogs (AOR: 2.52; 95% CI: 1.12-5.7), observed wild bird (AOR: 2.31; 95% CI: 1.01-5.3) were significant risk factor of AIV contamination at the stall levels in LBM. The study revealed a high level of AIV with H5 and H9 subtypes in the studied LBMs. We recommend one surveillance at LBMs for early detection of novel strains and improved biosecurity practices to prevent spillover of AIV to people or wild birds in the peri-urban and rural settings in Bangladesh.